Methodologies for Reliability Evaluation of Network - Arya R.; Koshti A.; Verma A.; Khan B.; Arya L. (My University, 2025)
This chapter presents basic methods of reliability evaluation of network. Series and series parallel system have been discussed for reliability evaluation. Evaluations of reliability, failure density function of complex systems have been discussed. Reliability evaluations of partially redundant system have been described. Four basic methodologies i.e. event space method, decomposition method, tie-set and cut-sets have been described to determine reliability function of complex network. At the end of few illustrative examples have been presented to have a better understanding of the techniques. © 2024 by The Institute of Electrical and Electronics Engineers, Inc. All right reserved.